PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM RUMAH TAHFIDZ (STUDI KASUS PADA LAZNAS PPPA DAARUL QUR’AN MALANG) - Dewi, Trisna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The Zakat, Infaq, Alms Fund (ZIS) functions to channel funds to community groups who are unable or mustahik in community empowerment or are only given consumptive funds for direct consumption. ZIS funds can also be channeled for educational costs in the form of scholarships for poor people. This research aims to determine community empowerment through the tahfidz house program at LAZNAS PPPA Daarul Qur'an Malang. This research uses a qualitative approach. This research is an activity that requires conducting a survey in the field to identify information and conditions carried out there. For this reason, the appropriate approach is qualitative because it can reveal various information with careful and meaningful description-analysis, providing complex details about phenomena that are difficult to express. the tahfidz house program at LAZNAS PPPA Daarul Qur'an Malang makes a significant contribution to community empowerment, especially in the field of education.